LOGICAL NEGATION AND BIOLOGICAL DEATH - Jurijus Radovičius (Problemos)
Postmodernist philosophy dissolves the concept of objective reality and by this also the concept of objective ethical obligation. Parmenides introducted an absolute difference between outer world and transcendent ideal being. This methods of an absolute formal logical negation was repeated by Epicuros in his discrimination between "we" and "death". Both object and subject as well as verges between them are flexible and may be subjective. The only absolute and objective difference is the opposition between our existence and non-existence. Formal logical negation along with the whole science was possible only thanks to biological death’s absoluteness. Being is not simply copula in judgement, as I. Kant thought, it is an autonomous logical projection of our own objective being or non-being. It is in this way being is a value and "ought" follows from "is".